Exploitation as Domination: What Makes Capitalism Unjust - Nicholas Vrousalis (Oxford University Press, 2022)
The exploitation of human by human is a globally pervasive phenomenon. Slavery, serfdom, and the patriarchy are part of its lineage. Guest and sex workers, commercial surrogacy, precarious labour contracts, sweatshops, and markets in blood, vaccines or human organs, are some contemporary manifestations of exploitation. What makes these exploitative transactions unjust? And is capitalism inherently exploitative? This book offers answers to these two questions. In response to the first question, it argues that exploitation is a form of domination, self-enrichment through the domination of others. On the domination view, exploitation complaints are not, fundamentally, about harm, coercion or unfairness. Rather, they are about who serves whom and why. Exploitation, in a word, is a dividend of servitude: the dividend the powerful extract from the servitude of the vulnerable. In response to the second question, the book argues that this servitude is inherent to capitalist relations between consenting adults; capital just is monetary title to control over the labour capacity of others. It follows that capitalism, the mode of production where capital predominates, is an inherently unjust social structure.
Keywords: 330; exploitation; domination; egalitarianism; negative liberty; positive liberty; republican liberty; origins of capitalism; imperialism; G.A. Cohen; David Schweickart; John Rawls; John Roemer; Karl Marx